PEMANFAATAN AIR KELAPA (Cocos nucifera) UNTUK MASKULINISASI IKAN GUPPY (Poecilia reticulata) - Sefti Heza Dwinanti; M. Hanggara Putra; Ade Dwi Sasanti (Universitas Sriwijaya, 2018)
ABSTRACT Masculinization is a method of sex reversal technique that can direct sexuality from female to male. The purpose of this study was to determine the effects of coconut water on masculinization in guppy by immersion administration. The study used a completely randomized design (CRD) with three treatments and three replications. After 12 days post spawning, female guppies were immersed for 8 hours.The concentrations were : 0%(P0), 20% (P1), and 40% (P2). The parameters were observed including percentage of male, survival rate and water quality (thermal, pH and kalium concentration). Baby guppies were reared until sex can be determined which were 42 days of culture. The result showed that the percentage of male guppy fish was 54.44% (P0), 77.78% (P1) and 90.00% (P2). The survival rate of larval during maintenance was 100% for all treatments. Water quality during maintenance was 27.0-28.40C for temperature and 6.38-7.20 for pH. To sum up, this experiment proved that coconut water can be used for masculinization by immersed pregnant female broadstock and it produced 90% male when immersed with 40% of coconut water. Keywords : Coconut water, guppy (Poecilia reticulata), masculinization